Comparative Studies on Multi-Component Pharmacokinetics of Polygonum multiflorum Thunb Extract After Oral Administration in Different Rat Models - Ma, Ninghui; Zhang, Yong; Sun, Liyan; Zhao, Yuan; Ding, Yue; Zhang, Tong (Frontiers in Pharmacology, 2021)
The clinical use of Polygonum multiflorum Thunb (PM) has been restricted or banned in many countries, due to its hepatotoxic adverse effects. Its toxicity research has become a hot topic. So far, the pharmacokinetic studies of PM, focusing on prototype compounds such as 2,3,5,4'⁃tetrahydroxystilbene⁃2⁃O⁃β⁃D⁃glucoside (TSG), emodin, and physcion, have been considered the main basis of pharmacodynamic material or of toxic effect. However, pharmacokinetic studies of its phase II metabolites have not yet been reported, mainly because the quantifications of such metabolites are difficult to do without the reference substance. In addition, pharmacokinetic studies on different pathological models treated with PM have also not been reported. In the present work, a simultaneous quantitation method for eight prototypes components of PM and their five phase II metabolites has been performed by ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) and used for the pharmacokinetic study of PM in two different liver pathological models in rats (normal, alpha-naphthylisothiocyanate (ANIT), and carbon tetrachloride (CCl4)). The results showed that the main blood-entering components of PM are TSG, emodin, physcion, emodin-8-O-β⁃D⁃glucoside (E-Glu), physcion-8-O-β⁃D⁃glucoside (P-Glu), aloe-emodin, gallic acid, resveratrol and catechin, among which TSG, emodin, and catechin were primary metabolized in phase II, while resveratrol was converted to all phase II metabolites, and the others were metabolized as drug prototypes. Meanwhile, their pharmacokinetic parameters in the different models also exhibited significant differences. For instance, the AUC (0-∞) values of the TSG prototype and its phase II metabolites were higher in the ANIT group, while the AUC (0-∞) values of the emodin prototype and its phase II metabolites were higher in the CCl4 group. To further illustrate the reasons for the pharmacokinetic differences, bilirubin metabolizing enzymes and transporters in the liver were measured, and the correlations with the AUC of the main compounds were analyzed. TSG and aloe-emodin have significant negative correlations with UGT1A1, BSEP, OATP1A4, OCT1, NTCP, MRP2 and MDR1 (p<0.01). These data suggest that when the expression of metabolic enzymes and transporters in the liver is inhibited, the exposure levels of some components of PM might be promoted in vivo.